"Just trying to live our lives" : gay, lesbian and bisexual students' experiences of being "at home" in university residence life - Munyuki, Chipo Lidia (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2016)
Higher education in South Africa is faced with a paramount task to help erode the social and structural inequalities that have been inherited from the Apartheid system (Department of Education 1997; Council on Higher Education 2000:12). The findings from the Soudien Report (2008:116-117) point out that the post-Apartheid higher education system in South Africa is characterised by various forms of discrimination and institutional cultures that marginalise some members of institutions resulting in pervasive feelings of alienation. In the South African higher education field, the concept of a "home" for all has been used by a variety of commentators to depict a vision of what transformed, inclusive higher education institutional cultures might look like. In this thesis, I interpret the experiences of residence life on the part of gay, lesbian and bisexual students on a largely residential campus. I ask how gay, lesbian and bisexual students experience being "at home" in the campus's residence system. The thesis is based on 18 in-depth qualitative interviews with students who self-identify as gay/lesbian or bisexual who have experienced residence life on the campus for a period longer than six months. A wide literature exists on the concept of "home" . Drawing from many different disciplines including anthropology, history, philosophy, geography, psychology, architecture and sociology, I distil the essential features of "at homeness" as incorporating comfort, privacy, security, acceptance, companionship and community. The research was concerned to inquire into how central the idea of home is to human flourishing and then into how gay, lesbian and bisexual students are routinely denied many of the essential comforts associated with being "at home" that heterosexual students have the privilege of taking for granted.
Keywords: Homosexuality and education -- South Africa; Gay students; Lesbian students; Bisexual students; Transsexual students; Student housing; Discrimination in higher education -- South Africa